Milheto submetido a diferentes adubações para a alimentação de codornas japonesas - Raimundo, Erikson Kadoshe de Morais (Universidade Federal de São Carlos, 2020)
Population growth has demanded the development of food production systems that meet the needs and preserve the environment. The aim of this research was to evaluate the agronomic and bromatological features of millet plants submitted to different fertilizations and, the effect of these, on the performance and quality of Japanese quail eggs fed with different millet inclusions. The plant development and bromatological characteristics of millet submitted to fertilization with cattle manure, organic compost and mineral fertilizer, plus a control, were evaluated. Plants submitted to fertilization with cattle manure showed a better response related to plant growth and productivity, however, there was no effect of fertilizations on the plant and grains bromatological composition. As there was no effect, the plants, regardless of the fertilization treatment, were included in the levels of 5, 10 and 15% in the diets for Japanese quails and the eggs performance and external and internal quality were analyzed. The inclusion of up to 10% of millet in the diets did not influence the egg quality. Millet production with organic fertilization has good crop reproductive development and can be used, as whole plant, in the composition of diets for Japanese quails, minimizing production investments.
Milet submitted to different fertilizers for japanese quails feeding
Keywords: Adubação orgânica; Composição bromatológica; Produção de ovos; Organic fertilization; Chemical composition; Egg production; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO